Measurements of the Angular Distribution of Elastically and Inelastically Scattered Products - Arazi, Andres; Abriola, Daniel Hugo (Springer, 2023)
Fil: Arazi, Andres. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina